Issues of state and national security: Religiously inspired terrorism in the Baltic States: internal and external factors - Anatolijs Kriviņš; Jānis Teivāns-Treinovskis; Vladas Tumalavičius (Insights into Regional Development)
Global terrorism has become one of the most serious threats to the security in the world today. The number of suspects arrested for religiously inspired terrorism in the EU Member States increased approximately five-fold between 2009 and 2018. The aim of the paper is to evaluate the threats of Religiously inspired terrorism in the three Baltic States - Estonia, Latvia and Lithuania. The study was conducted using the methods of academic literature, statistical data analysis and qualitative content analysis. This study has applied quantitative technique and qualitative technique to explore the relationship between religiously inspired terrorism and relevant factors - Internal factors, Legal migration, Illegal migration, Participation in international missions and operations, Traveling to regions where terrorist groups have a stronger presence, Student exchange programs and foreign students, Employees from other countries e.c. The study has determined that the level of terrorist threats in the Baltics has not changed in recent years and remains relatively low. The Baltic States today is not a target for religiously inspired terrorism. The level of internal threat from existing religious communities has been low and remains low. No significant terrorism-related incidents have occurred in Estonia, Latvia and Lithuania in previous years. There is no reason to believe that these internal risks will increase in the near future. In turn, there are significant long-term risks associated with external threats. A balanced and neutral policy towards all religious denominations should continue in all Baltic countries. As a primary task, the authors conducted an analysis of a number of theoretical and practical tax incentives assessment models.